2012
DOI: 10.1111/j.1600-0412.2011.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault and other types of violence in intimate partner relationships

Abstract: Sexual assaults are more likely to co-occur with some types of physical and psychological violence than with others. This knowledge may be important for improving our understanding of sexual violence in intimate partner relationships and in the efforts to detect intimate partner violence. Bruises, loss of hair and bite marks may suggest that sexual acts were committed against the victim's will.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…In agreement with previous studies [ 14 , 21 , 22 ], in this study sexually assaulted women were also more likely to report threatening or attempting suicide. This finding highlights the importance of mental health management, particularly regarding suicidal behaviour, and history of sexual assault [ 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…In agreement with previous studies [ 14 , 21 , 22 ], in this study sexually assaulted women were also more likely to report threatening or attempting suicide. This finding highlights the importance of mental health management, particularly regarding suicidal behaviour, and history of sexual assault [ 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…It has been found that 8.8% of women in the United States of America have been raped by their partners (Breiding, 2015), indicating that IPSV is a serious problem across different cultural contexts. Given that sexual violence can exist alongside physical and psychological violence, the health repercussions can become highly dangerous (Alsaker et al, 2011;Jaffe et al, 2017). However, though the prevalence and consequences of physical violence by partners have been widely documented, little is known about IPSV (Pengpid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Det er funnet assosiasjoner mellom seksuell vold og partnerdrap internasjonalt (12). Også i Norge er det funnet forbindelser mellom seksuell vold og alvorlig vold, for eksempel vold mot en gravid mage (14). Sammenhenger mellom ulike former for partnervold mot kvinner og helseproblemer er etter hvert grundig dokumentert, både nasjonalt og internasjonalt (4,(7)(8)(9)(10)(11)15).…”
Section: Seksuell Voldunclassified
“…I en studie blant kvinner ved norske krisesentre (14) var seksuell tvang fra partneren forbundet med annen alvorlig fysisk og psykisk vold, som vold mot gravid mage, dominans og isolasjon samt bitemerker, lugging og vridning av arm (14). Seksuell tvang opptrer i sammenheng med mange andre typer vold og svaert alvorlig vold, også i vårt befolkningsutvalg.…”
Section: Fysisk Vold Assosieres Med Seksuell Tvangunclassified